The Use of Perovskia abrotanoides Extract in Ameliorating Heat Stress-Induced Oxidative Damage and Improving Growth Efficiency in Carp Juveniles (Cyprinus carpio) - Hossein Adineh; Saeed Zahedi; Morteza Yousefi; Zeynab Sedaghat; Sevdan Yilmaz; Ebrahim Gholamalipour Alamdari; Mohammad Farhangi (Aquaculture Nutrition)
Herbal extracts have been successfully used as feed additives in fish culture with attractive growth-promoting, immunostimulant, antimicrobial, and antioxidant properties for several fish and shellfish species. Therefore, we have designed a feeding trial to assess the impacts of dietary incorporation of Perovskia abrotanoides extract (PAE) on common carp (Cyprinus carpio). For this purpose, five isonitrogenous (35% protein) and isocaloric (~4,000 kcal/kg) diets have been supplied by supplementing PAE at the varying inclusion levels as 0.0%, 0.25%, 0.5%, 1.0%, and 2.0% diets, and growth performance and feed utilization, digestive enzyme activities, serum biochemical variables, antioxidant responses, and immunological factors were studied. The experiment continued for 60 days. At the termination of the experiment, the mean final weight, weight gain percentage (WG%), feed conversion rate (FCR), and specific growth rate (SGR) have been improved significantly in all fish groups fed PAE-based diets with regard to those fed the reference diets. A second-order polynomial regression equations indicate that the optimum dietary supplementation level of PAE in fish diets was ~1%. Serum cortisol, glucose, triglyceride, cholesterol, and malondialdehyde levels as well as catalase, alanine aminotransferase, and aspartate aminotransferase activities were significantly decreased generally in all PAE-supplemented groups compared to the control groups before and/or after high-temperature stress (32°C). Moreover, serum total protein, albumin, and total immunoglobulin levels as well as ACH50, lysozyme, superoxide dismutase, and glutathione peroxidase activities were increased before and/or after high-temperature stress (32°C). In conclusion, the results showed, for the first time, that dietary supplementation with ~1% PAE can improve growth performance, stimulated the digestive enzymes, and enchanced antioxidant status as well as immune parameters and prevented high-temperature stress of common carp.